Inotuzumab ozogamicin in combination with low-intensity chemotherapy for older patients with Philadelphia chromosome-negative acute lymphoblastic leukaemia: a single-arm, phase 2 study. Issue 2 (February 2018) - Kantarjian, Hagop; Ravandi, Farhad; Short, Nicholas J; Huang, Xuelin; Jain, Nitin; Sasaki, Koji; Daver, Naval; Pemmaraju, Naveen; Khoury, Joseph D; Jorgensen, Jeffrey; Alvarado, Yesid; Konopleva, Marina; et al.
Summary: Background: Inotuzumab ozogamicin, an anti-CD22 monoclonal antibody bound to a toxin, calicheamicin, has shown single-agent activity in relapsed or refractory acute lymphoblastic leukaemia. We aimed to assess the activity and safety of inotuzumab ozogamicin in combination with low-intensity chemotherapy in older patients with acute lymphoblastic leukaemia. Methods: We did a single-arm, phase 2 study at the MD Anderson Cancer Center (Houston, TX, USA). Eligible patients were aged 60 years or older and had newly diagnosed, Philadelphia chromosome-negative, acute lymphoblastic leukaemia, and an Eastern Cooperative Oncology Group performance status of 3 or lower. The induction chemotherapy regimen used was mini-hyper-CVD (a lower intensity version of the conventional hyper-CVAD). Odd-numbered cycles (1, 3, 5, and 7) comprised intravenous cyclophosphamide (150 mg/m 2 every 12 h on days 1–3) and oral or intravenous dexamethasone (20 mg per day on days 1–4 and days 11–14); no anthracycline was administered. Intravenous vincristine (2 mg flat dose) was given on days 1 and 8. Even-numbered cycles comprised intravenous methotrexate (250 mg/m 2 on day 1) and intravenous cytarabine (0·5 g/m 2 given every 12 h on days 2 and 3). Intravenous inotuzumab ozogamicin was given on day 3 of the first four cycles at the dose of 1·3–1·8 mg/m 2 at cycle 1, followed by 1·0 −1·3 mg/m 2 in subsequent cycles. Maintenance therapy with dose-reduced POMP (purinethol [6-mercaptopurine], oncovin [vincristine sulfate], methotrexate, and prednisone) was given for 3 years. The primary endpoint of this study was progression-free survival at 2 years. Analyses were by intention to treat. The study is ongoing, recruiting patients for an approved expansion phase with a modified treatment plan by protocol amendment. The trial is registered with ClinicalTrials.gov, number NCT01371630 . Findings: Between Nov 12, 2011, and April 22, 2017, 52 patients with a median age of 68 years (IQR 64–72) were enrolled. With a median follow-up of 29 months (IQR 13–48), 2-year progression-free survival was 59% (95% CI 43–72). The most frequent grade 3–4 adverse events were prolonged thrombocytopenia (42 [81%] patients), infections during induction (27 [52%]) and consolidation chemotherapy (36 [69%]), hyperglycaemia (28 [54%]), hypokalaemia (16 [31%]), increased aminotransferases (ten [19%]), hyperbilirubinaemia (nine [17%]), and haemorrhage (seven [15%]). Veno-occlusive disease occurred in four (8%) patients. Six (12%) patients died from adverse events that were deemed treatment related (five [10%] from sepsis and one [2%] from veno-occlusive disease). Interpretation: Inotuzumab ozogamicin plus mini-hyper-CVD chemotherapy is a safe and active first-line therapy option in older patients with newly diagnosed acute lymphoblastic leukaemia and could represent a new therapy for this population. Randomised, phase 3 trials to evaluate the efficacy of this combination compared with the current standard of care in this setting, combination chemotherapy without inotuzumab ozogamicin, are warranted. Funding: MD Anderson Cancer Center.